Mathematics for business and economics - Nicholson, Robert H. (New York ; Singapore : McGraw-Hill, 1986)
An introduction to mathematical analysis. A review of basic concepts. Mathematical functions: an introduction. Linear functions. Systems of Linear equations and inequalities. Matrix algebra. Linear programming. Nonlinear functions. The mathematics of finance. Differential calculus: principles. Differential calculus: applications. Integral calculus with applications. Probability: principles and applications. Mathematical models and business analysis: a final word.
Keywords: Economics; Mathematics; Business mathematics; Economics, Mathematical; Business mathematics